2019
DOI: 10.1039/c8cc06500d
|View full text |Cite
|
Sign up to set email alerts
|

Formal [3+2] cycloaddition of vinylcyclopropane azlactones to enals using synergistic catalysis

Abstract: The present study reports the asymmetric cyclization of enals with vinylcyclopropane azlactones efficiently catalyzed by the combination of achiral Pd(0) complexes and chiral secondary amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Later, in 2016, Michelet and Vitale, [8a] J ø rgensen [8b] and Rios [8c] independently published asymmetric [3+2] cycloaddition between vinyl cyclopropanes and α , β ‐unsaturated aldehydes catalyzed by a combination of chiral secondary amine and palladium complex (Scheme 1a). The process proceeding through the formation of transient zwitterionic π‐allyl palladium intermediates and chiral α , β ‐unsaturated iminium ions was also successfully used for the enantioselective preparation of spirocyclic compounds containing oxindole, benzofuranone, Meldrum's acid, and azlactone motifs [8c,d] . In addition, we recently showed that pyrazolone‐fused dihydrooxepines could be activated with palladium generating similar zwitterionic π‐allyl palladium intermediate and used for the synthesis of spirocyclic pyrazolones in high enantio‐ and diastereoselectivity (Scheme 1b) [9] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, in 2016, Michelet and Vitale, [8a] J ø rgensen [8b] and Rios [8c] independently published asymmetric [3+2] cycloaddition between vinyl cyclopropanes and α , β ‐unsaturated aldehydes catalyzed by a combination of chiral secondary amine and palladium complex (Scheme 1a). The process proceeding through the formation of transient zwitterionic π‐allyl palladium intermediates and chiral α , β ‐unsaturated iminium ions was also successfully used for the enantioselective preparation of spirocyclic compounds containing oxindole, benzofuranone, Meldrum's acid, and azlactone motifs [8c,d] . In addition, we recently showed that pyrazolone‐fused dihydrooxepines could be activated with palladium generating similar zwitterionic π‐allyl palladium intermediate and used for the synthesis of spirocyclic pyrazolones in high enantio‐ and diastereoselectivity (Scheme 1b) [9] .…”
Section: Methodsmentioning
confidence: 99%
“…Compound 7 e was prepared in high yield (79%) without loss of optical purity. Similarly, ester 8 e prepared by Wittig olefination [8d] from 4 e , was achieved with retained enantiopurity. Another studied transformation of the prepared spirocyclic compound 4 e was the opening of thiazolone moiety.…”
Section: Methodsmentioning
confidence: 99%
“…In this reaction, the chiral prolinol silylether organocatalyst 19 was used to generate the highly activated α,β‐unsaturated iminium ion dipolarophile, and meanwhile induce the stereoselective formation of the five‐membered ring [39a] . This strategy was further extended to indane‐1,3‐dione‐derived‐, azalactonyl‐, dicyano‐ and cyanoester‐substituted vinylcyclopropanes [39b–e] …”
Section: Asymmetric Reactions Of Vinyl‐substituted Cyclopropanesmentioning
confidence: 99%
“…In 2019, the Veselý group reported asymmetric (3 + 2)-annulation of azlactone-based SVCPs 58 with α,β-unsaturated aldehydes 48 for the enantioselective synthesis of functionalized spirocyclic derivatives 59 and 59′ under cooperative catalysis ( Scheme 24 ). 29 After the extensive screening of various organo- and metal catalysts, high enantioselectivity with good conversion of the cycloadduct was attained by merging the chiral secondary amine L4 and the Pd(0) complex as the catalyst. The methodology was tolerated for a wide range of aryl and aliphatic substituents, delivering the desired products.…”
Section: Other Activated Spirocyclopropanesmentioning
confidence: 99%